2018
DOI: 10.3390/rs10030488
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics in Vegetation GPP over the Great Khingan Mountains Using GLASS Products from 1982 to 2015

Abstract: Gross primary productivity (GPP) is an important parameter that represents the productivity of vegetation and responses to various ecological environments. The Greater Khingan Mountain (GKM) is one of the most important state-owned forest bases, and boreal forests, including the largest primeval cold-temperature bright coniferous forest in China, are widely distributed in the GKM. This study aimed to reveal spatiotemporal vegetation variations in the GKM on the basis of GPP products that were generated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…The GLASS GPP product has been widely used to examine the spatial and temporal variations in GPP (Han et al 2015;Hu et al 2018;Ma et al 2015;Wang et al 2015;Xu et al 2013). For example, Yuan et al (2019) used the GLASS GPP product to investigate the impacts of atmospheric VPD on global terrestrial GPP and found persistent widespread decreases in GPP after the late 1990s due to increases in VPD, which offset the positive CO2 fertilization effect.…”
Section: Gross Primary Production (Gpp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The GLASS GPP product has been widely used to examine the spatial and temporal variations in GPP (Han et al 2015;Hu et al 2018;Ma et al 2015;Wang et al 2015;Xu et al 2013). For example, Yuan et al (2019) used the GLASS GPP product to investigate the impacts of atmospheric VPD on global terrestrial GPP and found persistent widespread decreases in GPP after the late 1990s due to increases in VPD, which offset the positive CO2 fertilization effect.…”
Section: Gross Primary Production (Gpp)mentioning
confidence: 99%
“…the MODIS FAPAR product, especially for croplands. Hu et al (2018) also incorporated the GLASS FAPAR product into their GPP calculations.…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports/ best-preserved and largest primeval forest in China, is one of the few locations in China with boreal forests 19 . It is also the southernmost boreal forest biome in the world 20 .…”
mentioning
confidence: 99%
“…Forest swamping was an important means of forest swamp formation in cold temperate regions. Dense canopy forests and the permafrost layers under the forests in cold temperate regions provided cold and wet conditions for swamp development [ 82 , 83 ]. Our results showed that forest swamping widely occurred under such conditions in the study area [ 84 ].…”
Section: Discussionmentioning
confidence: 99%